1988
DOI: 10.1111/j.1651-2227.1988.tb10762.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bronchial Asthma among Schoolchildren in a Swedish District

Abstract: The prevalence of asthma among 10,527 children aged 7-16 years was investigated in 1985. Children were assigned to the asthma group when replies to a questionnaire stated that at least two of four stipulated symptoms had been experienced in the preceding year. A validation study, comprising exploration of medical history, pulmonary auscultation and physiological tests (spirometry and methacholine inhalation challenge) was performed in 73 children. The overall prevalence of asthma was 4%. The most common sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
2
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 13 publications
2
11
2
1
Order By: Relevance
“…In contrast, less than 40% were exposed to cat allergen in their homes and only 17% were exposed to cockroach allergen. In areas where the allergen exposure pattern is different, other allergens are significantly and independently associated with disease (10,16,22,33). In Los Alamos, New Mexico, and Sweden, sensitization to allergens derived from domestic animals has been associated with asthma (10,33).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, less than 40% were exposed to cat allergen in their homes and only 17% were exposed to cockroach allergen. In areas where the allergen exposure pattern is different, other allergens are significantly and independently associated with disease (10,16,22,33). In Los Alamos, New Mexico, and Sweden, sensitization to allergens derived from domestic animals has been associated with asthma (10,33).…”
Section: Discussionmentioning
confidence: 97%
“…Some studies on asthma epidemiology have revealed what seems to be a geographic difference in the prevalence of asthma [2,12,13,18,[24][25][26][27]. In a review, COOKSON [11] concluded that there are true differences in cumulative prevalence of asthma-like illnesses between countries, and suggested that they could be explained by environmental variations.…”
Section: Comparison Between Centresmentioning
confidence: 99%
“…In a review, COOKSON [11] concluded that there are true differences in cumulative prevalence of asthma-like illnesses between countries, and suggested that they could be explained by environmental variations. In Sweden, a number of studies have focused on the prevalence of asthma [9,15,18,25,28], and in this country as well as some others it has been proposed that this prevalence might differ between regions [14,15,18]. ÅBERG [14] found the prevalence of asthma and allergic rhinitis to be highest among those born in the northernmost provinces of the country, and, in a recent study, LARSON et al [15] found differences both in reported respiratory symptoms and in the consumption of drugs for asthma, between two neighbouring counties.…”
Section: Comparison Between Centresmentioning
confidence: 99%
“…This is particularly the case for pollinosis, whereas pollen counts are usually higher in urban than in rural areas. Selection bias may act by selecting people who can live in the countryside (285,854,(962)(963)(964), but confounding factors are likely to exist.…”
Section: Variations In Allergy Prevalencementioning
confidence: 99%